Protection of Renewable Energy Systems - Hooshyar, Ali (University of Waterloo, 2014)
The recent progress in renewable energy (RE) technologies has led to the erection of RE power plants (REPPs) up to the order of several hundred megawatts. Unlike their predecessors, which generally appeared in the form of dispersed generation (DG) coupled mainly with distribution systems, such large REPPs are naturally part of high-voltage transmission networks and hold non-negligible proportions of the generation. On the other hand, RE-based DGs are becoming pervasive in modern distribution systems. As a result, the fault ride-through (FRT) requirement has become an essential part of modern grid codes. This dissertation investigates the challenges brought about by the FRT requirement now affecting protection of systems with which REPPs are integrated. On the transmission level, it explores the performance of distance relays that are installed at an REPP substation and protect the neighboring line. The analyses are founded upon time-domain simulation of detailed REPP models with FRT capability. The studies include squirrel cage induction generator and doubly-fed induction generator (DFIG)-based wind farms, as well as full-scale converter-interfaced REPPs. The exclusive fault behavior of REPPs is scrutinized to identify possible relay maloperations and their root causes. The relay malfunctions revealed by this dissertation are restricted to systems with REPPs, and are not among the known distance relay failures that can occur in conventional power systems. If a communication link with minimal bandwidth requirement is in place, distance relays provide non-delayed fast tripping over the entire length of the line. This feature is retained by devising modified relaying algorithms. On the distribution level, the dissertation examines the effects of RE-based DGs on directional relays and on fault type classification methods. DFIG-based wind turbines constitute an appreciable portion of today's DG power. Conventional directional elements are shown to be adversely affected when a distribution system incorporates DFIG-based wind DG. An effective method is proposed to identify the fault direction using the waveshape properties of fault signals. Microgrids are the building blocks of future smart distribution systems. Protective devices of smart and fault-resilient microgrids are not expected to trip the healthy phases during unbalanced short-circuits. Thus, some utilities as well as relay manufacturers have started contemplating single- and double-pole tripping for distribution systems. Selective phase tripping demands fault type classification. This dissertation reveals that existing industrial methods that exploit the phase difference between sequence currents and the magnitudes of phase and sequence currents misidentify the fault type in microgrids that include photovoltaic and/or Type IV wind DGs. Using phase and sequence voltages, two new classifiers are proposed to determine the fault type for not only microgrids with different DGs, but for any three-phase system.
Keywords: Renewable energies; Power system protection; Electrical and Computer Engineering